THEORETICO-LEGAL MODELS FOR HARMONIZING INTELLECTUAL PROPERTY RIGHTS AND NATIONAL SECURITY: INTERNATIONAL EXPERIENCE AND THE UKRAINIAN CONTEXT - Zapadynchuk, Vladyslav (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to identify and systematize, in a theoretico-legal perspective, the models for harmonizing intellectual property (IP) rights with national security requirements by comparing foreign approaches (the USA, the EU and multilateral fora) and adapting them to the Ukrainian context. Research methods: normative legal analysis (including Art. 73 of the TRIPS Agreement, the U.S. invention secrecy regime, and EU initiatives on crisis licensing), historical-legal and comparative approaches, system-structural modeling of the interactions between instruments and institutions, and analytic-synthetic procedures for generalizing empirical data and deriving recommendations. Results: three archetypes are distinguished – (1) patent secrecy as a mechanism to prevent leakage of critical technologies; (2) crisis IP governance (compulsory/open licensing) for rapid scale-up of essential developments; (3) “dual-track” corporate strategies that balance patents and know-how. It is shown that secrecy reduces disclosure risks but suppresses commercialization; crisis licensing accelerates access and production, yet increases intelligence and export-diversion risks in high-intensity conflicts; Ukrainian practice is fragmented (unclear declassification rules, no compensation for “secret patents,” limited support for private defense innovators). Discussion: a hybrid model for Ukraine is substantiated that provides for transparent secrecy and declassification procedures with fair remuneration to authors, flexible crisis-licensing tools with temporal and subject-matter safeguards, and a security-screened export policy; problematic issues for further debate are outlined – criteria and timelines for declassification, compensation and judicial-protection mechanisms, the limits of “open licensing commitments” in wartime, standards for choosing between patenting and know-how in the private defense sector, and the integration of IP governance into the national security architecture.